Time variation in asset price response to macro announcements - Linda S. Goldberg; Christian Grisse (Federal Reserve Bank of New York, 2013)
Although the effects of economic news announcements on asset prices are well established, theserelationships are unlikely to be stable. This paper documents the time variation in the responses of yield curves and exchange rates using high-frequency data from January 2000 through August 2011. Significant time variation in news effects is present for those announcements that have the largest effects on asset prices. The time variation in effects is explained by economic conditions, including the level of policy rates at the time of the news release, and risk conditions: Government bond yields increase in response to good news, but less so when risk is elevated. Risk conditions matter since they can capture the effects of uncertainty on the information content of news announcements, the interaction of monetary policy and financial stability objectives of central banks, and the effect of news announcements on the risk premium.
Keywords: E43; E44; E52; F31; G12; G14; G15; 330; macroeconomic news announcements; high-frequency data; bond yields; exchange rates; monetary policy; risk; Börsenkurs; Zinsstruktur; Wechselkurs; Zeit; Wirtschaftsinformation; Makroökonomischer Einfluss; Ankündigungseffekt; USA